Characteristics of Ground Coffee Quality on Variations in Temperature and Roasting Time for Robusta Coffee (Coffea Canephora Pierre Ex A.Froehner) Green Bean - Ade Ayu Oksari; Neneng Hasanah; Irvan Fadli Wanda; RTM Sutamihardja (Universitas Djuanda, 2023)
Robusta coffee beans dominate coffee plantations in Indonesia because they have superior properties and are fast-growing. Bogor Regency is one of the largest coffee producers in West Java and was selected to supply robusta coffee for this study. However, the quality of coffee beans still needs to improve. The quality of the coffee beans can be enhanced if the roasting process is carried out at the right temperature and roasting time. This study aims to determine the temperature and duration of roasting the optimum robusta coffee and roasted coffee grounds compared to the quality of branded coffee on the market. Robusta coffee beans roast using a stainless steel skillet with an iron thermometer. The temperature and roasting duration is 170° C, 180° C, and 190° C for 10 and 15 minutes. The robusta ground coffee from Cipanas was analyzed and compared with the branded coffee. Phytochemical tests showed robusta ground coffee samples containing secondary metabolites of alkaloids, flavonoids, saponins, and tannins. The temperature and roasting time of Bogor robusta coffee at 190 °C for 10 minutes gave the best results for several test parameters (moisture content, caffeine levels, pH, coffee content, ash content, and microbial contamination). The quality results obtained are to the requirements set by SNI 01-3542-2004. The quality of roasted ground coffee is the same as branded ground coffee. It is recommended that coffee producers use optimal roasting temperature and duration to improve the quality of their coffee products